Kur'an. Arapça. (İstanbul)
41, 281 sayfa, 39 sayfa
Keywords: “An outcome of IRCICA’s series of studies on earliest copies of the Holy Quran, this book throws light on the characteristics of the partial copy which is preserved at Bibliothèque Nationale de France, Paris. Though there is no information as to its date, it is certainly one of the earliest having reached our time, even older than some of those that are attributed to the times of the third and the fourth caliphs. The meticulous analytical study, done by Dr. Tayyar Altıkulaç, an authoritative scholar in Quranic studies, examines its features as to script, orthography and other technical criteria and compares them with those of other earliest Quran copies. The analytical text begins by an account of the fragment’s journey to Paris and an acknowledgement of earlier work on it, particularly the printing of 56 folios of it (out of 79 in the same library and more elsewhere) by François Déroche and Sergio Noja Noseda in 1998. Follows a page-by-page examination of the copy. This the fifth study published by IRCICA in this series. It will be followed by a study on a very early copy of the Quran: the fragment found at Tubingen University Library, Germany. Not only with its findings and scholarly observations but also with its methodology and coverage, this work is a valuable contribution to studies on the history of the dissemination of the Quran across the world“ -- Yayıncı.